It's not summer without you : a summer novel - Han, Jenny (New York : Simon & Schuster BFYR, 2011)
Teenaged Isobel "Belly" Conklin, whose life revolves around spending the summer at her mother's best friend's beach house, reflects on the tragic events of the past year that changed her life forever.
Wilson's Junior High School, October 2010
School Library Journal, April 2010
Publisher's Weekly, March 2010
Horn Book, October 2010
Kirkus Review, March 2010
Young Adult
Keywords: Interpersonal relations -- Juvenile fiction; Beaches -- Juvenile fiction; Summer -- Juvenile fiction; Vacation homes -- Juvenile fiction; Friendship -- Juvenile fiction; Coming of age -- Fiction; Interpersonal relations -- Fiction; Beaches -- Fiction; Summer -- Fiction; Vacation homes -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Beaches -- Fiction; Summer -- Fiction; Vacation homes -- Fiction; Friendship -- Fiction; Bildungsromans; Bildungsromans